The First Large Absorption Survey in H i (FLASH): I. Science goals and survey design - Allison, J.R.; Sadler, E.M.; Amaral, A.D.; An, T.; Curran, S.J.; Darling, J.; Edge, A.C.; Ellison, S.L.; Emig, K.L.; Gaensler, B.M.; Garratt-Smithson, L.; Glowacki, Marcin; et al. (CAMBRIDGE UNIV PRESS, 2022)
We describe the scientific goals and survey design of the First Large Absorption Survey in H i (FLASH), a wide field survey for 21-cm line absorption in neutral atomic hydrogen (H i) at intermediate cosmological redshifts. FLASH will be carried out with the Australian Square Kilometre Array Pathfinder (ASKAP) radio telescope and is planned to cover the sky south of at frequencies between 711.5 and 999.5 MHz. At redshifts between and (look-back times of 4-8 Gyr), the H i content of the Universe has been poorly explored due to the difficulty of carrying out radio surveys for faint 21-cm line emission and, at ultra-violet wavelengths, space-borne searches for Damped Lyman-absorption in quasar spectra. The ASKAP wide field of view and large spectral bandwidth, in combination with a radio-quiet site, will enable a search for absorption lines in the radio spectra of bright continuum sources over 80% of the sky. This survey is expected to detect at least several hundred intervening 21-cm absorbers and will produce an H i-absorption-selected catalogue of galaxies rich in cool, star-forming gas, some of which may be concealed from optical surveys. Likewise, at least several hundred associated 21-cm absorbers are expected to be detected within the host galaxies of radio sources at <![CDATA[$0.4 < z, providing valuable kinematical information for models of gas accretion and jet-driven feedback in radio-loud active galactic nuclei. FLASH will also detect OH 18-cm absorbers in diffuse molecular gas, megamaser OH emission, radio recombination lines, and stacked H i emission.